Simple Purification of Vetiver Oil by Multiglass Plate System for Quality Improvement - Evi Yanto; Egi Agustian; Anny Sulaswatty (Research Center for Chemistry - LIPI, 2016)
Vetiver oil is one of essential oil from Indonesia which no synthetic substitute is available. The drawback of vetiver oil from Indonesia is smoky odor and dark appearance. To increase added value of Indonesian vetiver oil, therefore it is need method with cheap production, simple and easy to operate. Multiglass plate system (MGS) is one method to increase added value of vetiver oil. The aim of this research is to improve the vetiver oil quality in terms of appearance, odor and the physicochemical properties by MGS method and also optimize the operation condition on the vetiver oil yield and total vetiverol contents. The process parameters used on this research are to optimize the flow rate, angular and amount of glass plate. As a result, was obtained the optimum condition in 0.38 ml/sec of flow rate, 3o of glass plate angular and 5 of glass plate to increase 15% of total vetiverol contents, while the yields decreased until 5.6%. Refined vetiver oil by MGS are almost meet fulfill with Indonesia National Standard number 06-2386-2006 except total vetiverol contents and odor. Even though, the total vetiverol content increased and the odor became slightly smoky compare to raw material. Based on the results, MGS method can give higher purification of vetiverol of increase vetiver oil quality with easy to handle, low cost operation and also can moved to anywhere due to portable unit and mobile system.